Design Fixation: A Comparison between Native and Foreign Domains - Mahesh, V.; Raja Shekar, P. V.; Pramod Kumar, P.; Kantha Reddy, M.; Ravichandran, Vishvaksena. (Journal of Engineering Education Transformations, 2015)
Design fixation negatively impacts design outcomes and is generally referred as the designer’s inability to consider multiple strategies to formulate and solve a design need. The present paper will assess some of the design skills of Indian engineering students viz. fluency, flexibility and originality. To evaluate these skills, a more general task of designing a disposable spill-proof coffee cup is given to the sample. The sample consisted of students from native domain (Mechanical and Civil engineering departments) and foreign domain (other than the mentioned departments). The results were discussed with reference to the level of fixation of students of native and foreign domains, while providing two different kinds of environments, one with a specified sample example and other with a design pattern.